If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7 + z)(4z + -9) = 0 Reorder the terms: (7 + z)(-9 + 4z) = 0 Multiply (7 + z) * (-9 + 4z) (7(-9 + 4z) + z(-9 + 4z)) = 0 ((-9 * 7 + 4z * 7) + z(-9 + 4z)) = 0 ((-63 + 28z) + z(-9 + 4z)) = 0 (-63 + 28z + (-9 * z + 4z * z)) = 0 (-63 + 28z + (-9z + 4z2)) = 0 Combine like terms: 28z + -9z = 19z (-63 + 19z + 4z2) = 0 Solving -63 + 19z + 4z2 = 0 Solving for variable 'z'. Factor a trinomial. (-7 + -1z)(9 + -4z) = 0Subproblem 1
Set the factor '(-7 + -1z)' equal to zero and attempt to solve: Simplifying -7 + -1z = 0 Solving -7 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1z = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1z = 0 + 7 -1z = 0 + 7 Combine like terms: 0 + 7 = 7 -1z = 7 Divide each side by '-1'. z = -7 Simplifying z = -7Subproblem 2
Set the factor '(9 + -4z)' equal to zero and attempt to solve: Simplifying 9 + -4z = 0 Solving 9 + -4z = 0 Move all terms containing z to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4z = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -4z = 0 + -9 -4z = 0 + -9 Combine like terms: 0 + -9 = -9 -4z = -9 Divide each side by '-4'. z = 2.25 Simplifying z = 2.25Solution
z = {-7, 2.25}
| 2(x+4)=x-5y | | 70+4=7 | | 66+74+110+17x+8=360 | | 8z=4Z-3+3Z | | 5(x-3)+6=5x | | 500=120+12n | | 15a+9a^3=0 | | 5x+6x+9x=180 | | 5.5+1.8X=2.8X | | 75=8-x | | 2w+2(3w+1)=22 | | 0.5x=0.35x | | y=-4x^2+95x | | 990+90+98+17x-3=360 | | x+(x+2)=52 | | 64w^2-49d^2=0 | | 5m+11= | | y=x(95-4x) | | 10/14=x/42 | | 4t+6-t=19 | | 6+0.1x=0.15x+8i | | 4a^2+12a=4 | | 100=8+x | | 10x+40-10x=12-24x | | 8w-w+7w= | | 6r=5r+r | | 2y+27=54 | | -7(-2y-9)+2(-6y+4)= | | 60+25x=35x+29 | | e^2k=3 | | 4x^4-9x^2-100=0 | | 8u-2=2u+8 |